Does liberalisation of air transport imply increasing competition? : lessons from the European case - Dobruszkes, F (Elsevier, 2009)
The liberalisation of European airspace opened up unprecedented freedoms to Community airlines. This theoretically allows for increased competition. This article inquires into the quantification and the geography of the services offered in Europe that enjoy competition. Undoubtedly, competition appears to have increased but has certainly not become the general rule, notably because liberalisation has led to the creation of many new air routes operated by a single airline. Competition primarily benefits passengers in the large European cities, as well as those in peripheral regions that receive major tourist flows from the big cities in the northern parts of Western Europe.